One and a Half Century of Diffusion: Fick, Einstein, Before and Beyond - Philibert, Jean (Diffusion Fundamentals, 2006)
The year 2005 gave us, through two anniversaries (1855 Fick and 1905 Einstein), the wish to go back to these authors’ seminal papers, whose aftermath had been (and still is) prodigious. This essay describes the contents of these articles: the macroscopic approach with Fick equations and the microscopic one with the Einstein-Smoluchowski random walk (Brownian motion) equation, while considering them in their historical context. Some further developments are briefly iscussed.